PWE-013 Should The Target TGN Range Be Different in Those with Intermediate Compared with Normal TPMT Activity?. (17th August 2016) - Johnston, EL; Warner, BD; Fong, SC; Ward, MG; Kariyawasam, V; Arenas-Hernandez, M; Marinaki, TM; Sanderson, JD; Blaker, PA
Abstract : Introduction: Thioguanine nucleotides (TGNs) are the biologically active metabolites of thiopurines. Methylated thiopurine metabolites (MeMPs) formed via thiopurine- S -methyltransferase (TPMT) may also have immunosuppressive properties through inhibition of de novo purine synthesis ( DNPS ). 1 Individuals with intermediate TPMT activity do not produce significant levels of methylated metabolites, with predictably less inhibition of DNPS and therefore may tolerate higher levels of TGNs. If confirmed this suggests that the therapeutic range of TGNs (240–450 pmol/8x10 8 ) may differ between patients with intermediate Vs normal TPMT activity. Methods: All IBD patients at Guy's and St Thomas' Hospitals treated with either azathioprine or mercaptopurine who had TGNs measured from 2002–2013 were included. Patients receiving low dose thiopurine with allopurinol were excluded. Data was collected using the electronic patient record system and statistical analysis was completed in GraphPad Prism version 5.0. Results: 2193 TGN measurements were included in the analysis, 340 (15.5%) from patients with intermediate TPMT activity and the remaining 1853 had normal TPMT activity. The average normalised thiopurine doses between groups was 1.13 Vs 1.87 mg/kg/day respectively, reflecting standard dose adjustment in intermediate TPMT patients. The median TGNs levels were significantly higher in patients with intermediate Vs normal TPMT activity; 370 Vs 277 pmol/8x10 8 (P = <0.00001) and the median MeMP levels were lower in patients with intermediate Vs normal TPMT activity; 104 pmol/8x10 8 RBC Vs 566 (P = <0.0001). No significant difference was found in the median values of Hb, WBCs, neutrophil or platelet counts between the groups. A lower lymphocyte count (1.3 Vs 1.2 x109/ 9 / L, P = 0.0010) and trend towards a higher MCV (93 Vs 94, P = 0.0625) was noted in patients with normal TPMT activity. Conclusion: Despite significantly higher TGN levels in patients with intermediate as compared to normal TPMT activity, there was no difference in levels of Hb, WBCs, neutrophil or platelets counts. This suggests a greater tolerance to TGNs in patients with intermediate TPMT activity and may indicate that a different TGN therapeutic range is needed in these patients. The likely reason is that methylated metabolites are biologically active and also play a role in overall thiopurine immunosuppression. Reference: 1 Tay BS, Lilley RM, Murray AW, et al . Inhibition of phosphoribosyl pyrophosphate amidotransferase from Ehrlich ascites-tumour cells by thiopurine nucleotides. Biochemical Pharmacology . 1969;18 (4):936–8. Disclosure of Interest: None Declared